HUBUNGAN FAKTOR YANG MENYEBABKAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS GUGUAK PANJANG KOTA BUKITTINGGI TAHUN 2017 - Anggraini, Yuliza (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
According to World Health Organization (WHO), overall anemia found in pregnancy was 51%, while anemia found in women was 35%. Based on the result of Basic Health Research (Riskesdas) in 2013, the anemia prevalence in pregnant mother in Indonesia was 37,1%. In Bukittinggi, it was posted that there were 38,61% anemic cases and 3,54% anemic cases in Guguak Panjang. Based on the data found in Department of Public Health of Bukittinggi, it revealed that the highest anemic cases in pregnant mother were in Guguak Panjang Bukittinggi Public Health Center.The research method used in this research was KMO factor analysis and Bartlett’s test to know the main factor towards the level of anemic cases by giving questionnaire to 53 respondents in working area of Guguak Panjang Public Health Center.The result of this research shows that the main factor of the four factors taken by the researcher to know the factors of anemic cases in pregnant women in the working area of Guguak Panjang Public Health center in 2017 was parity. It was based on the result of the test using Measure of Sampling Adequacy factor analysis.It can be concluded that parity influences the anemic cases, especially in the first pregnancy. For the health party, it is recommended to enhance early detection towards the pregnant mothers who are susceptible to anemia. Keywords: Anemia, pragnancy woman